Dynamics and control of entrainer enhanced reactive distillation using an extraneous entrainer for the production of butyl acetate. (January 2018) - Cho, Minjeong; Han, Myungwan
Highlights: Dynamics of reactive distillation using an extraneous entrainer that form a binary or ternary azeotrope mixture is analyzed. Control schemes for the entrainer-enhanced reactive distillation, based on different dynamics with the type of azeotrope formed by the entrainer, are proposed. Abstract: This paper introduces the dynamics and control of entrainer-enhanced reactive distillation(ERD) for the efficient production of n-butyl acetate via esterification reaction of butanol and acetic acid. It was recently reported that using an extraneous instead of the internal entrainer (butyl acetate) could considerably improve the process efficiency (Cho et al., 2014). In the ERD system, different multiplicities were found to appear depending on whether the azeotrope that the entrainer forms with water is binary or ternary. In the case of binary azeotrope formation, the extraneous entrainer only takes the role of entrainer if the liquid level of the organic phase in the decanter is controlled. However, in the case of ternary azeotrope formation, both the extraneous entrainer and butyl acetate can take the role of entrainer. Keeping a proper inventory of the extraneous entrainer in the column was crucial for ensuring that the system was at a high conversion steady state, leading to a high butyl acetate yield. This is mainly because the presence of too much extraneous entrainer in the reactive distillation column results in a drop in the reaction yield. We propose two different control schemes depending on the type of azeotrope that the extraneous entrainer forms with the reaction mixture. The proposed control schemes were demonstrated to be effective in maintaining a high reaction yield and product purity.